RESULTS OF SURGICAL TREATMENT DEPENDING ON THE VOLUME OF OPERATION IN PATIENTS WITH DIFFERENTIATED THYROID CANCER - Tillyashaikhov M.N; Khakimov G.A; Abdurakhimov O.N; Malikov M.A (European Science Publishing, 2024)
Based on the study, it was established that the volume surgical intervention, in contrast to the surgical technique, is one of the most important prognostic factors. The optimal scope of surgery in patients with differentiated thyroid cancer should be the removal of the entire thyroid gland with tissue and lymph nodes at level VI of the neck [1].